MEMAHAMI PERBEDAAN INDIVIDU PEBELAJAR DALAM PROSES BELAJAR MENGAJAR - Wahidah (Fakultas Tarbiyah dan Ilmu Keguruan, 2019)
The purpose of writing this article is to explain how education that understands the uniqueness of each student in individual learning or individual instruction. This writing method uses a descriptive analysis approach from a number of literatures from journals, books and other documents. There are four aspects of individual differences that must be considered by teachers and principals in a teaching and learning process that includes physical-motor differences, intelligence differences, differences in language skills, and psychological differences. Understanding individual differences here is by carrying out individualized instruction (individual learning). Also provides opportunities for children to learn independently (Independent Study) by developing individual learning (individual instruction) in accordance with the level of their needs.